Maleimide‐styrene‐butadiene terpolymers: acrylonitrile‐butadiene‐styrene inspired photopolymers for additive manufacturing. Issue 7 (11th January 2022) - Steindl, Johannes; Ehrmann, Katharina; Gorsche, Christian; Huang, Ching‐Chung; Koch, Thomas; Steinbauer, Patrick; Rohatschek, Andreas; Andriotis, Orestis G.; Thurner, Philipp J.; Prado‐Roller, Alexander; Stampfl, Jürgen; Liska, Robert
Abstract: The terpolymer acrylonitrile‐butadiene‐styrene (ABS) is a widely used thermoplastic material due to its excellent mechanical properties, especially high toughness. However, the monomer system of ABS cannot be feasibly photopolymerized due to its reactivity, opacity and monomer volatility. We show the transfer of an ABS microstructure to photopolymers via monomer systems designed to mimic ABS while remaining photopolymerizable. Acrylonitrile was substituted by more reactive and less volatile maleimides, of which the N substituent influences crosslinking considerably. Instead of styrene, less volatile derivatives were utilized as comonomers. Poly(butadiene) was introduced as cheap, readily available and non‐volatile rubber. The resulting maleimide‐styrene‐poly(butadiene) networks exhibit varying microphase separations and simultaneous transparency. While optimized materials cannot quite exhibit the yield strain of hot‐pressed ABS filament, their toughness partly exceeds that of ABS. Superior thermal stabilities and glass transition temperatures up to 190 °C were observed. Finally, stereolithographic printing of one tuned monomer system was conducted. © 2021 The Authors. Polymer International published by John Wiley & Sons Ltd on behalf of Society of Industrial Chemistry. Abstract : The monomer system consisting of maleimides, styrenes and the toughening component poly(butadiene) was developed to obtain an acrylonitrile‐butadiene‐styrene inspired, phase separated yet transparent photopolymer, which is suitable for dynamic light processing 3D printing.